The effects of caries removal techniques on volume-loss percentage and microtensile bond strength - KANAR, ÖZLEM; TAĞTEKİN, DİLEK; KORKUT, BORA (My University, 2024)
Purpose: This study aimed to calculate the volume loss percentages (VLP) regarding the ICDAS II system and various caries removal techniques (CRT) and to assess the microtensile bond strength (μTBS) in terms of VLP following CRT. Materials and methods: Three-dimensional data of human extracted molars were acquired with an extraoral dental scanner (Ineos x5, Dentsply Sirona) before and after the caries removal. Each ICDAS score group (0,3,4 and 5) was divided into four subgroups according to the CRT: stainless steel bur (Group S), ceramic bur (Group C), tungsten carbide bur (TCB) and air abrasion (AA) with bioactive-glass (Group TB), and TCB and AA with Al2O3 (Group TA). Pre and post-caries removal data were overlaid in a 3D modeling software and were volumetrically measured (n=10). Following the restoration, samples were prepared with non-trimming technique and subjected to microtensile testing. Results: ICDAS II scores were found related the VLP (p< 0.001) and the μTBS (p<0.001). CRT was not effective on VLP (p=0.110), whereas CRT type was significant on μTBS (p<0.001). In Group TA, a strong negative correlation was observed between the μTBS and the VLP for ICDAS 5 score (r=-0.919; p=0.027). Conclusions: ICDAS II can provide a preliminary indication for the amount of VLP and reduction in μTBS following caries removal. The use of 29 μm Al2O3 with air abrasion in deep caries removal may improve μTBS while potentially reducing the VLP. Key words: air abrasion, caries removal technique, dental scanner, microtensile bond strength, volume loss

Çürük uzaklaştirma yöntemlerinin hacim kaybi ve bağlanma üzerindeki rolü. Amaç: Bu çalışmada, ICDAS II sistemi ve çeşitli çürük uzaklaştırma yöntemlerine (CRT) ilişkin hacim kaybı yüzdelerinin (VLP) hesaplanması ve CRT sonrası mikrogerilim bağlanma kuvvetinin (μTBS) VLP açısından değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: İnsan çekilmiş büyükazı dişlerinin, çürük uzaklaştırma öncesinde ve sonrasında ağız dışı dental tarayıcı (Ineos x5, Dentsply Sirona) ile üç boyutlu kayıtları alındı. Her bir ICDAS skor grubu (0,3,4 ve 5) CRT'ye göre dört alt gruba ayrıldı: paslanmaz çelik frez (Grup S), seramik frez (Grup C), tungsten karbit frez (TCB) ve biyoaktif cam ile air abrazyon (Grup TB), ve TCB ve Al2O3 ile air abrazyon (Grup TA). Çürük uzaklaştırma öncesi ve sonrası kayıtlar 3D modelleme yazılımında (Meshmixer, Autodesk, ABD) çakıştırıldı ve hacimleri hesaplandı (n=10). Restorasyonun ardından non-trimming tekniğiyle hazırlanan numuneler mikrogerilim testine tabi tutuldu. Bulgular: VLP ve μTBS, ICDAS II skor gruplarına göre anlamlı farklılıklar gösterdi. (p<0.001) . CRT tipi VLP üzerinde etkili olmazken (p=0.110), μTBS üzerinde ise CRT etkisi anlamlıydı (p<0.001). Grup TA'da μTBS ile ICDAS 5 skor grubundaki VLP arasında güçlü negatif korelasyon görüldü (r=-0,919; p=0,027). Sonuç: ICDAS II sistemi, çürüğün uzaklaştırılmasını takiben hacim ve bağlanma dayanımındaki değişiklikleri öngörmeyi sağlayabilir. Derin çürüklerin uzaklaştırılmasında air abrazyon ile 29 μm Al2O3'ün kullanılması bağlanmayı arttırırken hacim kaybını azaltabilir.Anahtar Kelimeler: air abrazyon, çürük uzaklaştırma yöntemi, hacim kaybı, mikrogerilim bağlanma kuvveti.
Keywords: air abrasion; caries removal technique; dental scanner; microtensile bond strength; volume loss; air abrazyon; çürük uzaklaştırma yöntemi; hacim kaybı; mikrogerilim bağlanma kuvveti